Jejak Flora dalam Festival Encek : Kajian Etnobotani Tumbuhan Ritual di Desa Sumbersekar, Malang - Irma Nur Ramadhania; Charisma Mayang Kholisotun; Ray Tunjung Sari; Rifdah Hanani Erviana; Fahrul Ghani Muhaimin; Karin Anindita Widya Pitaloka; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to document and preserve the local community's knowledge regarding the use of ritual plants in the Encek Festival. This study focuses on identifying the types, habits, parts used, methods of use, philosophical meanings, and conservation efforts of the plants used in the Encek Festival. This study uses a qualitative descriptive approach. Data were collected through interviews, observation, and documentation. This study involved a number of informants who were determined gradually through purposive sampling, followed by snowball sampling until data saturation was reached. The data obtained was then analyzed descriptively with reference to Miles and Huberman's analysis stages, namely data reduction, data presentation, and conclusion drawing. The results of the study show that the Encek Festival utilizes 10 plant species from 8 families, dominated by tree habitus, with flowers as the most widely used part and generally arranged in ritual processions. These plants have philosophical meanings as symbols of spirituality to God. The conservation status of most species is classified as Not Evaluated, while several others are classified as Least Concern, indicating a relatively low risk of extinction. Based on how they are obtained, the plants used come from cultivation and purchase, so their use does not directly put pressure on plant populations. This study confirms that the Encek Festival plays an important role in preserving ethnobotanical knowledge while maintaining the sustainability of local cultural values amid the dynamics of modernization.